2012 IEEE International Symposium on Radio-Frequency Integration Technology (RFIT) 2012
DOI: 10.1109/rfit.2012.6401651
|View full text |Cite
|
Sign up to set email alerts
|

A 77 GHz CMOS low noise amplifier for automotive radar receiver

Abstract: This paper presents the design of a low noise amplifier (LNA) for automotive radar application operating at 76-77 GHz. The LNA consists of 5 cascade common source amplifiers. The output of each stage is positioned close to the gate of the next stage creating a LC resonance output load, therefore complex interstage matching networks are eliminated. Moreover, transmission lines (T Ls) are utilized to create matching and load inductors. As a result, chip size is significantly reduced. The proposed LNA is implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This FOM includes the most relevant parameters for evaluating LNAs for low‐power, high‐gain, low‐noise, and wideband applications. Table is a summary of the implemented 57–81 GHz CMOS LNA, and recently reported state‐of‐the‐art CMOS and SiGe BiCMOS LNAs with operation frequency around 77 GHz in . It is noteworthy that our LNA exhibits both low P DC and one of the lowest NFs and highest FOMs.…”
Section: Measurement Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This FOM includes the most relevant parameters for evaluating LNAs for low‐power, high‐gain, low‐noise, and wideband applications. Table is a summary of the implemented 57–81 GHz CMOS LNA, and recently reported state‐of‐the‐art CMOS and SiGe BiCMOS LNAs with operation frequency around 77 GHz in . It is noteworthy that our LNA exhibits both low P DC and one of the lowest NFs and highest FOMs.…”
Section: Measurement Results and Discussionmentioning
confidence: 98%
“…Lately, although several studies have reported excellent 77 GHz (or switchable 60/77‐GHz dual‐band) CMOS and SiGe BiCMOS LNAs , as a whole, the performances of these LNAs are not adequate. For instance, in , a single cascode stage 77–81 GHz LNA in 0.13 µm SiGe BiCMOS process with current‐gain cutoff frequency/maximum oscillation frequency ( f T / f max ) of 230/280 GHz was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the number of stages can exceed three [2]- [5]. Therefore, the situation of cascading stages needs to be considered for LNA design at mm-wave frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The basic requirements of a LNA include good input and output impedance matching (S 11 and S 22 ), high reverse isolation (S 12 ), high forward gain (S 21 ), a low noise figure (NF) and high power linearity (or phase linearity) and low power consumption (P DC ). Recently, several excellent 77-81 GHz (or 76-77 GHz) CMOS/BiCMOS LNAs have been reported [1][2][3]. However, the overall performances of these LNAs are not satisfactory.…”
mentioning
confidence: 99%